PENGARUH STORE ATMOSPHERE DAN KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN DI WARKOP PINGGIRAN 45PEKANBARU - Syalisah, Ulfa; Sri, Restuti; Taufiqurrahman, Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study was to find out the effect of the influence of store atmosphere and service quality on customer satisfaction and loyalty at Warkop Pinggiran 45 Pekanbaru. This study uses a quantitative approach. The sample in this study were 140 people who had visited Warkop Pinggiran 45 Pekanbaru more than 2 times and were aged 17 years and over. Sampling using nonprobability sampling method and purposive sampling technique. The research instrument used a questionnaire and analyzed using path analysis through SPSS. The results showed that, Store Atmosphere, Service Quality has a significant impact on customer satisfaction and customer loyalty. Customer satisfaction has a significant effect on customer loyalty. Store atmosphere and service quality has a significant effect on customer loyalty with customer satisfaction as an intervening variable.Keywords: Store Atmosphere, Service Quality, Customer Satisfaction and Customer Loyalty